Turning office workers into "MacGyvers" : improving personal resilience in an organization case UPM Raflatac - Maijala, Aino (2017)
Office work today has been found to be much more emotionally demanding than in the past. The current environment in which organizations operate is full of turbulence and competitive pressure, which influences the employees as well. Businesses are in constant search of different ways of making their staff more productive to increase the efficiency of their companies. Resilience, which stands for an ability to bounce back from adversity and stressful situations, is therefore called for in the positions of many office workers. This research aims at finding out what the role of the organization is in the resilience of its employees. Recognizing and utilizing the most effective ways of improving the staff’s resilience would presumably increase not only the level of performance of the staff but also of the entire company. In order to spot the different factors in an organization to affect the employees’ resilience, a mixed methods research was conducted in a case company. Resilience tests were first arranged in the company to collect quantitative data on the sample, but the emphasis of the study was on the semi-structured interviews that provided a qualitative approach on the matter. The focus of the study was on the group of professional and managerial staff, that consists of different kinds of knowledge workers and specialists. The results suggest that there are both positive and negative factors in an organization that affect the staff in terms of resilience. Increasing awareness of resilience and providing tools for improving it is one of the most important actions that a company’s management can take. However, it was also noticed that by buffering some of the negative factors in the business environment, the process can be further supported. Change proved out to be a highly negative factor in the company, which is why an increase in the flow of information, managerial support and visibility of management would be recommended. Resilience could also be utilized in recruiting for positions with a high risk of adversity and in team building to increase diversity and thus make more valuable teams.